HTC One (M8) for dummies - Hughes, Bill (John Wiley & Sons, 2015)
HTC One (M8) For Dummies is a practical user's guide to the HTC One (M8) device, covering a range of pragmatic and how-to topics, from the most useful features and tricks of the core applications to techniques to get the most out of your smartphone. Approaching the capabilities of the HTC One (M8) from the point of view of a user who is intimidated by the technology, and perhaps a bit baffled by the documentation and online support that come with the phone, this handy guide covers all aspects of the HTC One (M8) in a familiar and friendly tone.